Investigating the Effect of TiO2, CaCO3, and Al2O3 on Mechanical Properties of LDPE Polymer Composites Fabricated by Injection Moulding Technique - Dinesh , K. R.; Hatti, Gururaj (Technological Innovation in Engineering Research Vol. 4, 2022)
The present work is analysis of CaCO3, Al2O3 & TiO2 reinforced LDPE composite, which are moulded into the shape of the die prepared according to ASTM standard using injection moulding machine on a low budget, which can be functioned with a smaller amount of effort. The prepared specimens are tested for various mechanical properties. The characterization and production of Polymer Matrix composites which can be used as artificial bone implant materials are described in this study. Artificial bone materials can be used to heal or replace damaged bone. Many implant materials have been developed in the previous three decades, including metal alloys, ceramics, polymers, and other materials. Stress shielding and bone regeneration are the key issues with metallic bone implants. Polymeric bone implants may overcome these difficulties. Due to their cost effectiveness, greater strength and ease of fabrication, polymer composites are noticeable candidate almost in all areas. However, when they are used in their original form they possess very low wear resistance and hardness. The present investigation gives information on mechanical properties of polymer matrix composites where LDPE (Low density polyethylene) is used as polymer matrix and TiO2, Al2O3 and CaCO3 are used as reinforcements. The samples were prepared according to ASTM standards by injection moulding machine with varying percentage of reinforcements in polymer matrix. Tests viz., tensile, flexural impact are carried out.